Pengembangan E-LKPD IPS Kelas V Berbasis Model Pembelajaran RADEC (Read, Answer, Discuss, Explain, Create) Materi Letak dan Kondisi Geografis Indonesia - Windy Anisa Dewi; Aquami Aquami; Ayu Nur Shawmi; Yulia Tri Samiha; Siti Fatimah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop E-LKPD social studies class V based on RADEC learning model (Read, Answer, Discuss, Explain, Create) material location and geographical conditions of Indonesia that is valid and practical. The type of research used is research and development model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques, namely questionnaires, observations, interviews, and documentation. The results of data analysis of the media validation level, namely design expert validation is categorized as very valid with a percentage of 90%, linguist validation is categorized as valid with a percentage of 80%, and material expert validation is categorized as very valid with a percentage of 90%. From the validation results, a total percentage of 86.66% was obtained in the valid category. The results of data analysis on the level of practicality of the media, namely the one to one trial obtained a percentage of 88.75% with a very practical category, and the small group trial obtained a percentage of 91.5% with a very practical category. From the trial results, a total percentage of 90.12% was obtained in the very practical category. Based on the research results, the E-LKPD social studies class V based on the RADEC learning model developed is suitable for use in the learning process.